2018
DOI: 10.1111/ddg.13605
|View full text |Cite
|
Sign up to set email alerts
|

Position paper: Telemedicine in occupational dermatology – current status and perspectives

Abstract: Teledermatology is the use of telecommunication technologies to exchange medical information for diagnosis, consultation, treatment and teaching in dermatology. While its use has been evaluated in a wide range of dermatological diagnoses, only few studies exist on its validity, diagnostic precision, feasibility, and cost-effectiveness in occupational dermatology. However, these studies show a considerable potential for diagnosis, prevention, treatment support and follow-up of patients with occupational skin di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 35 publications
(35 reference statements)
0
24
0
4
Order By: Relevance
“…Additionally, prior research already contended the positive relationship between person-job fit and employees’ work engagement ( De Beer et al, 2016 ; Enwereuzor et al, 2016 ; Bui, 2017 ). According to the norm of reciprocity and social exchange theory ( Cropanzano and Mitchell, 2005 ), employees are supposed to pay back when they got resources and support. State directly, employees will find their job worthwhile to when their needs have been satisfied and the demands of the job also match their knowledge, skills and abilities.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Additionally, prior research already contended the positive relationship between person-job fit and employees’ work engagement ( De Beer et al, 2016 ; Enwereuzor et al, 2016 ; Bui, 2017 ). According to the norm of reciprocity and social exchange theory ( Cropanzano and Mitchell, 2005 ), employees are supposed to pay back when they got resources and support. State directly, employees will find their job worthwhile to when their needs have been satisfied and the demands of the job also match their knowledge, skills and abilities.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…[7][8][9] Two different forms of teledermatological applications are distinguishable: 'store and forward' (S&F) applications describe applications in which data are stored and retrieved time and location independently, whereas 'live interaction' (LI) applications avail direct communication between at least two stakeholders using videoconferences. 8,10,11 Hybrid forms combine S&F and LI. 2 Due to the increased administrative effort in coordinating live conferences, S&F is the more frequently used method.…”
Section: Introductionmentioning
confidence: 99%
“…A good example of this was provided by two meta-analytic reviews, which demonstrated that both distributive and procedural justice were positively correlated with trust in one’s organization and supervisor ( Colquitt et al, 2001 , 2013 ). More importantly, social exchange theory (SET) research showed that organizational trust was a mediator of the relationship between organizational justice and work outcomes, such as organizational citizenship behavior ( Konovsky and Pugh, 1994 ; Aryee et al, 2002 ; Cropanzano and Mitchell, 2005 ; Colquitt et al, 2012 , 2013 ; van Dijke et al, 2018 ). Although the relationship between justice and trust and the mediating role of trust in the association of justice with certain positive outcomes have only been demonstrated in an organizational context, based on the effects of social justice and political trust on public cooperation, we expect that political trust, following social justice, can boost public cooperation in a social context.…”
Section: Introductionmentioning
confidence: 99%